ANALISIS KESESUAIAN SARANA PENYELAMATAN DIRI PADA PT PERUSAHAAN LISTRIK NEGARA DI BALIKPAPAN - Siboro, Impol; Noeryanto, Noeryanto; Hardiyono, Hardiyono; Regina Yeusy , Olga (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
Rescue facilities are facilities used by residents and firefighters in an effort to save human lives and property in the event of a fire in a building and the environment. Based on the Regulation of the Minister of Public Works No. 26 of 2008 concerning Technical Requirements for Fire Protection Systems in Buildings and the Environment, self-rescue facilities consist of means of escape, emergency stairs, emergency lighting, evacuation route signs and temporary gathering places. In this case, PT Perusahaan Listrik Negara in Balikpapan, especially PT PLN (Persero) UP3 Balikpapan, has a multi-storey building consisting of 3 floors and there are several sources of danger such as the number of flammable materials in the room such as office furniture, office stationery, electronic equipment. and also flammable archival documents. The purpose of this study was to determine the suitability of the means of escape at the PT Perusahaan Listrik Negara building in Balikpapan. This study uses a descriptive method with a qualitative approach, to determine the suitability of the means of escape at the PT PLN (Persero) UP3 Balikpapan building, namely making descriptive by conducting field observations using a checklist form and conducting interviews with informants, then the results are analyzed using the percentage of conformity criteria assessment. From the results of the study, it was found that the value of the suitability of egress facilities was 100%, emergency stairs 75%, emergency lighting 83%, evacuation route signs 86%, temporary gathering places 60% with an average value of the suitability of self-rescue facilities in the PT PLN (Persero) UP3 building. Balikpapan is 80.8% with good category.